Bioactive Triterpenoid Saponins From the Seeds of Aesculus chinensis Bge. var. chekiangensis - Zhang, Nan; Wei, Shuxiang; Cao, Shijie; Zhang, Qiang; Kang, Ning; Ding, Liqin; Qiu, Feng (Frontiers in Chemistry, 2020)
Phytochemical investigation of Aesculus chinensis Bge. var. chekiangensis (Hu et Fang) Fang obtained 33 triterpenoid saponins, including 14 new ones, aesculiside C–P (1–14). The structure elucidations were performed through comprehensive MS, 1D and 2D-NMR analysis, and their absolute configuration was unambiguously determined by X-ray diffraction analysis as well as Mo2(OAc)4-induced ECD method for the first time. All the substances were examined for their cytotoxic activities against three tumor cell lines, Hep G2, HCT-116, and MGC-803. Of these, compounds 8, 9, 14–16, 18, and 22 exhibited potent cytotoxicities against all cell lines with IC50 of 2–21 μM, while compounds 3, 6, 7, 17–19, 20, 24, and 28 depicted moderate activity (IC50 13 to >40 μM). On these bases, the preliminary structure-activity correlations were also discussed. Meanwhile the neuroprotective properties of triterpenoid saponins from Aesculus genus were evaluated for the first time. Among them, compounds 1, 4, 12, 20, 22, 25, 29, and 31 exhibited moderate activities against COCl2-induced PC12 cell injury.